Fabrication of Robust Superhydrophobic Bamboo Based on ZnO Nanosheet Networks with Improved Water-, UV-, and Fire-Resistant Properties. (4th May 2015) - Li, Jingpeng; Sun, Qingfeng; Yao, Qiufang; Wang, Jin; Han, Shenjie; Jin, Chunde
Abstract : Bamboo with water-resistant, UV-resistant, and fire-resistant properties was desirable in modern society. In this paper, the original bamboo was firstly treated with ZnO sol and then hydrothermally the ZnO nanosheet networks grow onto the bamboo surface and subsequently modified with fluoroalkyl silane (FAS-17). The FAS-17 treated bamboo substrate exhibited not only robust superhydrophobicity with a high contact angle of 161° but also stable repellency towards simulated acid rain (pH = 3) with a contact angle of 152°. Except for its robust superhydrophobicity, such a bamboo also presents superior water-resistant, UV-resistant, and fire-resistant properties.